2014
DOI: 10.1200/jco.2013.53.7142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Doxorubicin and Cyclophosphamide Versus Single-Agent Paclitaxel As Adjuvant Therapy for Breast Cancer in Women With 0 to 3 Positive Axillary Nodes: CALGB 40101 (Alliance)

Abstract: Purpose Optimal adjuvant chemotherapy for early-stage breast cancer balances efficacy and toxicity. We sought to determine whether single-agent paclitaxel (T) was inferior to doxorubicin and cyclophosphamide (AC), when each was administered for four or six cycles of therapy, and whether it offered less toxicity. Patients and Methods Patients with operable breast cancer with 0 to 3 positive nodes were enrolled onto the study to address the noninferiority of single-agent T to AC, defined as the one-sided 95% upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 15 publications
2
62
0
2
Order By: Relevance
“…The tolerability of XT was better in NSABP-B40 when these agents were administered before AC (21). Even with 70% of the patients having node-positive disease, the number of DFS events was much lower than expected, as has been observed in a number of adjuvant breast cancer trials (27)(28)(29)(30). This low event rate substantially decreased the power of the study to show superiority of the AC!XT arm.…”
Section: Discussionmentioning
confidence: 77%
“…The tolerability of XT was better in NSABP-B40 when these agents were administered before AC (21). Even with 70% of the patients having node-positive disease, the number of DFS events was much lower than expected, as has been observed in a number of adjuvant breast cancer trials (27)(28)(29)(30). This low event rate substantially decreased the power of the study to show superiority of the AC!XT arm.…”
Section: Discussionmentioning
confidence: 77%
“…Also taxanes have significant toxic side effects, especially polyneuropathy. It has been shown that anthracycline-free regimens are not inferior to anthracyclines [3]. The question arises whether patients require both chemotherapy components and whether some patients might be sufficiently treated with anthracycline or taxanes alone.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the single-agent paclitaxel failing to show non-inferiority to AC, favorable toxicity profile and only 1% OS absolute difference made paclitaxel a reasonable option for unfit patients needing chemotherapy [59].…”
Section: Triple Negative Ebcmentioning
confidence: 99%